Prime Archives in Endocrinology 2020
DOI: 10.37247/paendo.1.2020.8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Toxicity: A Clinical Perspective

Abstract: saturation of the capacity of vitamin D binding protein. Increased public awareness of vitamin D-related health benefits might increase the risk of VDT due to self-administration of vitamin D in doses higher then recommended for age and body weight or even higher than the established upper limit intake values. Consequently, the incidence of hypercalcemia due to hypervitaminosis D might increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…As a result of excessive intake of vitamin D, serum levels of vitamin D metabolites (25(OH)D; 24,25(OH)2D; 25,26 (OH)2D; and 25(OH)D‐26,23‐lactone) increase and exceed vitamin D binding protein binding capacity, causing the increase of free active metabolite 1,25(OH) 2 D. This vitamin D metabolite reaches the vitamin D receptor (VDR) in the nucleus of cells and increases calcium absorption and bone mobilisation by causing exaggerated gene expression. As a result, it causes hypercalcemia and hyperphosphatemia, resulting in iPTH suppression 26 . While the most common cause of vitamin D‐associated hypercalcemia is iatrogenic supplementation, production of ectopic 1,25‐dihydroxyvitamin D (sarcoidosis, tuberculosis, fungal diseases, granulomatous diseases such as leprosy, and lymphoma) can cause inactivating mutations of the CYP24A1 gene 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of excessive intake of vitamin D, serum levels of vitamin D metabolites (25(OH)D; 24,25(OH)2D; 25,26 (OH)2D; and 25(OH)D‐26,23‐lactone) increase and exceed vitamin D binding protein binding capacity, causing the increase of free active metabolite 1,25(OH) 2 D. This vitamin D metabolite reaches the vitamin D receptor (VDR) in the nucleus of cells and increases calcium absorption and bone mobilisation by causing exaggerated gene expression. As a result, it causes hypercalcemia and hyperphosphatemia, resulting in iPTH suppression 26 . While the most common cause of vitamin D‐associated hypercalcemia is iatrogenic supplementation, production of ectopic 1,25‐dihydroxyvitamin D (sarcoidosis, tuberculosis, fungal diseases, granulomatous diseases such as leprosy, and lymphoma) can cause inactivating mutations of the CYP24A1 gene 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hypercalcemia, vitamin D intoxication can cause several symptoms such as depression, stupor, and coma psychiatrically; short QT, bradyarrhythmia, and hypertension in the cardiovascular system; nausea, vomiting, constipation, peptic ulcer, and pancreatitis in the gastrointestinal tract; and hypercalciuria, nephrocalcinosis, and renal failure in the kidneys 28 . In addition to 25(OH)D level >150 ng/mL biochemically, vitamin D intoxication can be symptomatic; hypercalcemia, hypercalciuria, and parathyroid hormone suppression can be seen 26 . Some studies have observed that in cases with vitamin D intoxication and hypervitaminosis, vitamin D level and serum calcium levels were not associated, and most of the cases were normocalcemic 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid therapy (prednisone or prednisolone) has also been the cornerstone of management of 1,25-dihydroxyvitamin mediated hypercalcemia. It lowers the calcium level by reducing intestinal calcium absorption by decreasing transcellular active transport processes, increasing urinary excretion of calcium and altering the hepatic vitamin D metabolism to favor synthesis of inactive metabolites [ 24 ]. Second line therapy of VDT includes phenobarbital, ketoconazole, or aminoquinolones [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…e Endocrine Society states that vitamin D toxicity is defined as 25(OH)D concentrations exceeding 375 nmol/L [19], with levels above this toxic threshold associated with the onset of hypercalcemia [19][20][21]. Signs and symptoms of vitamin D intoxication are directly related to the effects of hypercalcemia [17,20,22], including decreased oral intake, nausea, vomiting, constipation, weakness, lethargy, and generalized malaise [17,20,21]. Hypercalcemia and vitamin D toxicity can lead to serious complications including renal failure, hypertension, and nephrocalcinosis [17,23,24].…”
Section: Discussionmentioning
confidence: 99%